If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 27 + 2(3f + -19) Reorder the terms: 0 = 27 + 2(-19 + 3f) 0 = 27 + (-19 * 2 + 3f * 2) 0 = 27 + (-38 + 6f) Combine like terms: 27 + -38 = -11 0 = -11 + 6f Solving 0 = -11 + 6f Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-6f' to each side of the equation. 0 + -6f = -11 + 6f + -6f Remove the zero: -6f = -11 + 6f + -6f Combine like terms: 6f + -6f = 0 -6f = -11 + 0 -6f = -11 Divide each side by '-6'. f = 1.833333333 Simplifying f = 1.833333333
| 9x^2+20x+364=0 | | 0.08(6+x)=0.12x+0.12 | | 2x+3+2x-4=78 | | 200-x/6=500-x/6 | | 2x+7.5=x | | (x^2-1)(x^2-9)=0 | | 3xy^2+yx=0 | | 7.50x-8=60.50 | | -15+z=-16 | | 6x-60=-2x+20 | | 2v-6+4v=0 | | 5n*5n+16=61 | | 7-5x=2x+3 | | x*4/5=7/20 | | x*5/4=7/20 | | 8p-8+2p=-18 | | -50x^2+x^4+49=0 | | -2=7-2m-7m | | 5x-22=3(x+2) | | 9+2z-3=6z+8-3z | | x*2/3=1/10 | | 7y-7-5y+2=0 | | 1/4=8^3x-7 | | 12y+6=6(6g+9) | | 2x/4=28 | | 2/5(x-1)x/2-5 | | 4b-3=-5 | | 32n=113 | | 2/5(x-1)x-2-5 | | 9+19n-7=9n+50-6n | | f(-x)=4x^2+5x+8 | | -3y-3=-1y-4 |